HYDROPHYSICAL MESOSTRUCTURE OF A COASTAL UPWELLING - Monin A.S.; Ozmidov R.V.; Paka V.T. (My University, 1987)
A coastal upwelling is produced by long-shore winds that generate drift currents If the Coriolis force deflects these away from shore, then the ebb flow of surface waters results in an upwelling. The authors use as an example data on the Canary Upwelling. The Joint-1 experiment found in it horizontal temperature gradients on the sea surface of the order of 0.5 deg/km at distances of 100 to 200 km off the coast of Africa. It was also found that the water of the upwelling is separated from the open ocean by a frontal zone located above the continental slope. This frontal zone in general follows the coast-line and the isobaths, with temperature differences δT approximately 13°C and salinity differences δS approximately 0.33 promilles (horizontal temperature gradients of less than 0.7 deg/km; salinity made a considerable contribution to the density difference on the front). Meandering of the front and an alternation of time periods with and without upwelling (as a result changes in wind) were common.